On-Chip Synthesis of Hyaluronic Acid-Based Nanoparticles for Selective Inhibition of CD44+ Human Mesenchymal Stem Cell Proliferation - Enrica Chiesa (Pharmaceutics, 2020)
In this study, an innovative microfluidics-based method was developed for one-step synthesis of hyaluronic acid (HA)-based nanoparticles (NPs), by exploiting polyelectrolytic interactions between HA and chitosan (CS), in order to improve reliability, reproducibility and possible scale-up of the NPs preparation. The on-chip synthesis, using a staggered herringbone micromixer, allowed to produce HA/CS NPs with tailored-made size and suitable for both parenteral (117.50 ± 4.51 nm) and loco-regional (349.15 ± 38.09 nm) administration, mainly composed by HA (more than 85% wt) with high negative surface charge (< −20 mV). HA/CS NPs were successfully loaded with a challenging water-insoluble molecule, Everolimus (EVE), an FDA- and EMA-approved anticancer drug able to lead to cell cycle arrest, reduced angiogenesis and promotion of apoptosis. HA/CS NPs resulted to be massively internalized in CD44+ human mesenchymal stem cells via CD44 receptor-mediated endocytosis. HA/CS NPs selectiveness towards CD44 was highlighted by blocking CD44 receptor by anti-CD44 primary antibody and by comparison to CS-based NPs cellular uptake. Eventually, high effectiveness in inhibiting cell proliferation was demonstrated on-chip synthetized EVE loaded HA/CS NPs by tracking in vitro DNA synthesis.